Sodium-Poor, Hydroxyl-Rich, Defective Na2Ti3O7 Prepared by γ-Irradiation and Its Enhanced Proton Conductivity - Tosapol Maluangnont; Tanagorn Sangtawesin; Phieraya Pulphol; Orawan Khamman; Pakpoom Reunchan; Kazuma Gotoh; Naratip Vittayakorn (Inorganic Chemistry, 2024)
is 1 order of magnitude larger than that in the nonirradiated sample; the relaxation time decreases from 30 to 2-6 μs with γ-irradiation. The γ-dose dependence of dielectric loss is also present and analyzed using the Jonscher universal power law, indicating the low-frequency dispersion behavior characteristics of high charge densities.
Keywords: Nuclear materials and radiation effects; Advancements in Battery Materials; Advanced Battery Materials and Technologies